Symposium 6: Bridging the Gap between Technical and Pedagogical Project-Partners' Perspectives on the Modelling of Communities of Practice - El Ghali, Adil; Giboin, Alain; Vanoirbeek, Christine (Proceedings of the International Conference on Networked Learning, 2008)
During the modelling process in multidisciplinary context, the points of view of the actors can be a barrier to efficiently achieve the process. In this paper, we relate the experience we have been confronted to in the context of the Palette IST project . In this project, computer scientists and educational scientists aim at developing services for communities of practice (CoPs). The common work following a participatory design methodology allow us to produce some interesting results for the CoPs, but require to bridge the gap between our perspectives and objectives.